Design, Development and Evaluation of Enteric Coated Tablets of Famotidine - Mishra, Prashansa; Shukla, Ankita; Rajput, Dharmendra Singh; Gupta, Naveen; Sharma, Neeraj K (Asian Journal of Pharmaceutical Research and Development, 2023)
The aim of the present study was to formulate and evaluate of enteric coated Famotidine sodium sesquihydrate tablets by using manotol, dicalcium phosphate, microcrystalline cellulose, crossrmelose sodium, magnesium starate and talc. FT-IR study was carried out to check any possible interactions between the drug and the excipients manotol, dicalcium phosphate, microcrystalline cellulose, crosscarmelose sodium, Famotidine sodium sesquihydrate were prepared by direct compression method using different concentration of, Avicel PH (MCC) as filler, mannitol and dicalcium phosphate as diluents, croscarmellose sodium as disintegrating agents, magnesium stearate and talc was used as a glidant and lubricant respectively. The granules were evaluated for the precompression parameters like angle of repose, bulk density, tapped density and compressibility index. The flow characteristics of the granules were assessed by determining their angle of repose and Carr’s Index. The values of compressibility index and angle of repose signify good flowability of the granules for all the batches. This shows that the granules had smooth flow properties ensuring homogenous filling of the die cavity during the compression (punching) of tablets.